Neuropilin and Neuropilin Associated Molecules as New Molecular Targets in Pancreatic Adenocarcinoma - H. Muders, Michael (Anti-Cancer Agents in Medicinal Chemistry, 2011)
The Neuropilin receptors are increasingly recognized as receptors for vascular endothelial growth factors like VEGF-A and VEGF-C as well as other important growth factors like HGF and FGF in human vasculature and in tumor cells. More and more studies show an important role of Neuropilin in cancer biology suggesting that these transmembrane proteins might be an emerging target for new therapies in different subsets of cancer. Interestingly, blocking the adaptor protein GIPC1/Synectin that interacts with Neuropilin might be another interesting avenue for therapy. This review summarizes unfolding scientific data on these receptors and its interacting protein GIPC1/Synectin as molecular targets for therapy in pancreatic ductal adenocarcinoma.
Keywords: GIPC1